Analysis of learning difficulties in reading, writing, and counting (Calistung) in upper elementary school: A case study - Umalihayati Umalihayati; Rina Yuliana; Laksmi Evasufi Widi Fajari; Syarifah Aini; Vivit Nurhikmah Havita; Ardaneswari Putri Cahyaningsih; Puji Rahayu Ningsih; Sulistia Ningrum; Gladisya Audita Azzahra; Halimatus Sa'diyah (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2024)
Reading, writing, and counting (calistung) are fundamental skills taught early to students and have become a significant issue in the learning process of upper elementary classes faced by teachers at the primary school level. This study aims to analyze the learning difficulties in calistung and the efforts made by schools and teachers to address these difficulties in upper elementary school students. The research method employed is qualitative, using a case study approach with data collection techniques including observation, interviews, and document analysis. The research sample consisted of upper elementary students (grades IV to VI) who experienced difficulties in calistung, selected through purposive sampling. The data analysis technique involved stages such as data collection, data reduction, data presentation, and drawing conclusions. The research findings indicate the presence of calistung learning difficulties among upper elementary school students, which include pre-academic and academic learning difficulties influenced by internal and external factors. Pre-academic learning difficulties involve deviant student behavior and language development disorders, while academic learning difficulties encompass challenges in reading, writing, and counting. The study suggests that calistung learning difficulties in upper elementary schools can be addressed through teachers designing effective learning activities based on student needs and providing counseling services for students facing learning challenges.